Impact of microwaves on colorimetric evaluation and morphological characteristics of wheat, flour and gluten (Research, Society and Development, 2021)
Physical processes have been increasingly used to replace processes that use chemical agents to treat grains. Thus, this study aimed to evaluate wheat grains that were subjected to microwave processing on the morphological characteristics of the treated wheat grains, wheat flours and their respective glutens, through instrumental color analysis, optical microscopy (MO) and scanning electron microscopy (SEM). The results showed significant changes for comparison among means by Scott-Knott test (p≤0.05), for the wheat treated by microwave from treatments at 100 W/54 min (TM 1), 450 W/18 min (TM 2) and 750 W/10 min (TM 3), obtaining higher and statistically different values, in the yellow (+b*) and red (+a*) regions, when compared with the same parameters for the control wheat (TC). The total color differences found (ΔE) between microwave-treated wheat and control wheat, which were in the range of 8.94 to 14.83, whose total color differences in relation to control wheat can be classified as very perceptible and possible to be differentiated visually. In the analyzed wheat flours from the microwave treatments at 100 W/54 min (FM 1), 450 W/18 min (FM 2) and 750 W/10 min (FM 3) for the luminosity parameter (L*) of instrumental color, being lower than the luminosity of the control wheat flour (FC). Through the evaluation of morphology by optical microscopy and scanning electron it was possible to identify the changes caused by microwave processing in the structures of wheat grain, in wheat flour and it becomes more evident in the protein matrix of lyophilized gluten, which presents expressive damage in gluten from wheat treated at 450 W/18 min (GM 2) and 750 W/10 min (GM 3). Thus, we can conclude that the evaluation of the morphology in the studied materials provides important tools that complement the classic determinations of physical, physical-chemical and rheological analyzes.